FORMULATION AND PROCESS OPTIMIZATION OF MUFFIN PRODUCED FROM COMPOSITE FLOUR OF CORN, WHEAT AND SWEET POTATO [Formulasi dan Optimasi Proses Produksi Mufin dari Tepung Komposit Jagung, Gandum dan Ubi Jalar] - Stefani Hartono; Eko Hari Purnomo; Azis B. Sitanggang; Denny S. Agustin; Purwiyatno Hariyadi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
Intensification of use of local carbohydrate sources such as corn and sweet potato is expected to minimize wheat import and support food diversification program. The objective of this research was to optimize the composite flour composition and baking process conditions in muffin production. This research was divided into 3 steps namely formula optimization using mixture design techniques, process optimization using response surface methodology and final product analysis. The formula and process optimization was based on sensory parameter using hedonic rating test involving 70 untrained panelists. The results showed that the optimum formula was a formula with 4% wheat flour, 86% corn flour, and 10% sweet potato flour. The optimum baking condition was 39 minutes at 157°C. Analysis of muffin made with the optimum formula and baking conditions showed that the muffin had hardness, moisture, ash, protein, fat, cabohydrate, and crude fibre of 107.3 gf, 23.22%, 1.83%, 5.89%, 22.46%, 69.82%, and 0.26%, respectively.